Chemical constituents of fresh‐cut potato as affected by cultivar, age, storage, and cooking. Issue 5 (21st April 2021) - Dite Hunjek, Draženka; Pelaić, Zdenka; Čošić, Zrinka; Pedisić, Sandra; Repajić, Maja; Levaj, Branka
Abstract : Abstract: Certain changes in phenolics and sugars can occur during the storage of potatoes, where particularly amounts of sugars represent the critical factor as they are involved in potentially harmful acrylamide (AA) formation during frying. This research investigates the impact of cultivars (Birgit and Lady Claire), tuber's age (1, 5, and 9 months), and storage duration (1, 5, and 8 days at 10 °C) on the content of phenolics and sugars in raw, boiled, and fried fresh‐cut potato (FCP). The influence of these factors on the formation of AA in fried FCP was also assessed. Significant differences in phenolics and sugars were observed between cultivars (cv. Birgit contained 5.77 mg of phenolics 100 g –1 of dry weight (DW) and 1.75 g of sugars 100 g –1 DW, while cv. Lady Claire contained 10.13 mg of phenolics 100 g –1 DW and 0.65 g of sugars 100 g –1 DW). The content of phenolics significantly decreased, while sugars increased during tubers' aging. FCP storage time had no significant influence on the content of phenolics and sugars. The phenolics and sugars were the highest in the raw samples and the lowest in the boiled ones. Although the AA level in fried samples was significantly influenced by cultivar (Birgit > Lady Claire) and it increased with FCP storage time, it was below European Food Safety Authority (EFSA) regulation's approved maximum value (750 µg kg –1 FW) in both cultivars. Therefore, cvs. Birgit and Lady Claire could be considered as promising FCP cultivars and for frying purposes. Practical Application: The results of this research reveal that quantitative changes of chemical constituents occurring during storage and cooking of fresh‐cut slices of potato cultivars Birgit and Lady Claire are not a concern. This is of particular importance to fresh‐cut producers and customers. Phenolics were reduced during storage, but they were still present in all cooked samples independently of the cooking method. The analysis of sugars showed that tubers as old as 9 months could be used for fresh‐cut potato processing, providing safe frying without critical levels of acrylamide.